Chest Tube Management: Past, Present, and Future Directions for Developing Evidence-Based Best Practices. Issue 1 (January 2023) - Lobdell, Kevin W.; Engelman, Daniel T.
In the field of modern cardiothoracic surgery, chest drainage has become ubiquitous and yet characterized by a wide variation in practice. Meanwhile, the evolution of chest drain technology has created gaps in knowledge that represent opportunities for new research to support the development of best practices in chest drain management. The chest drain is an indispensable tool in the recovery of the cardiac surgery patient. However, decisions about chest drain management—including those about type, material, number, maintenance of patency, and the timing of removal—are largely driven by tradition due to a scarcity of quality evidence. This narrative review surveys the available evidence regarding chest-drain management practices with the objective of highlighting scientific gaps, unmet needs, and opportunities for further research. Visual abstract